Ultra High Performance Liquid Chromatography Method for the Determination of Two Recently FDA Approved TKIs in Human Plasma Using Diode Array Detection - Marwa Fouad; Maxime Helvenstein; Bertrand Blankert (Journal of Analytical Methods in Chemistry)
Generally, tyrosine kinase inhibitors have narrow therapeutic window and large interpatient variability compared to intrapatient variability. In order to support its therapeutic drug monitoring, two fast and accurate methods were developed for the determination of recently FDA approved anticancer tyrosine kinase inhibitors, afatinib and ibrutinib, in human plasma using ultra high performance liquid chromatography coupled to PDA detection. Diclofenac sodium was used as internal standard. The chromatographic separation was achieved on an Acquity UPLC BEH C18 analytical column using a mobile phase combining ammonium formate buffer and acetonitrile at a constant flow rate of 0.4 mL/min using gradient elution mode. A µSPE (solid phase extraction) procedure, using Oasis MCX µElution plates, was processed and it gave satisfying and reproducible results in terms of extraction yields. Additionally, the methods were successfully validated using the accuracy profiles approach (β = 95% and acceptance limits = ±15%) over the ranges 5–250 ng/mL for afatinib and from 5 to 400 ng/mL for ibrutinib in human plasma.